Restoring mucosal barrier function and modifying macrophage phenotype with an extracellular matrix hydrogel: potential therapy for ulcerative colitis - Keane, Timothy J.; Dziki, Jenna; Sobieski, Eric; Smoulder, Adam; Castleton, Arthur A; Turner, Neill J.; White, Lisa J.; Badylak, Stephen F. (Oxford Academic Press, 2017)
Background & Aims: Despite advances in therapeutic options, more than half of all patients with ulcerative colitis (UC) do not achieve long-term remission, many require colectomy, and the disease still has a marked negative impact on quality of life. Extracellular matrix (ECM) bioscaffolds facilitate the functional repair of many soft tissues by mechanisms that include mitigation of pro-inflammatory macrophage phenotype and mobilization of endogenous stem/progenitor cells. The aim of the present study was to determine if an ECM hydrogel therapy could influence outcomes in an inducible rodent model of UC. Methods: The dextran sodium sulfate (DSS)-colitis model was used in male Sprague Dawley rats. Animals were treated via enema with an ECM hydrogel and the severity of colitis was determined by clinical and histologic criteria. Lamina propria cells were isolated and the production of inflammatory mediators was quantified. Mucosal permeability was assessed in-vivo by administering TRITC-dextran and in-vitro using transepithelial electrical resistance (TEER). Results: ECM hydrogel therapy accelerated healing and improved outcome. The hydrogel was adhesive to colonic tissue, which allowed for targeted delivery of the therapy, and resulted in a reduction in clinical and histologic signs of disease. ECM hydrogel facilitated functional improvement of colonic epithelial barrier function and the resolution of the pro-inflammatory state of tissue macrophages. Conclusions: The present study shows that a nonsurgical and nonpharmacologic ECM-based therapy can abate DSS-colitis not by immunosuppression but by promoting phenotypic change in local macrophage phenotype and rapid replacement of the colonic mucosal barrier